2021
DOI: 10.1093/bib/bbab173
|View full text |Cite
|
Sign up to set email alerts
|

A new thinking: extended application of genomic selection to screen multiomics data for development of novel hypoxia-immune biomarkers and target therapy of clear cell renal cell carcinoma

Abstract: Increasing evidences show the clinical significance of the interaction between hypoxia and immune in clear cell renal cell carcinoma (ccRCC) microenvironment. However, reliable prognostic signatures based on a combination of hypoxia and immune have not been well established. Moreover, many studies have only used RNA-seq profiles to screen the prognosis feature of ccRCC. Presently, there is no comprehensive analysis of multiomics data to mine a better one. Thus, we try and get it. First, t-SNE and ssGSEA analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 66 publications
2
40
0
Order By: Relevance
“…found that the hypoxia-immune risk score was negatively associated with EREG-mRNAsi and ENHsi. Higher EREG-mRNAsi and ENHsi levels meant better prognosis ( 10 ). In this study, Cluster 2 was found to be relevant to lower TSIs ( Supplementary Figure S2C ).…”
Section: Resultsmentioning
confidence: 99%
“…found that the hypoxia-immune risk score was negatively associated with EREG-mRNAsi and ENHsi. Higher EREG-mRNAsi and ENHsi levels meant better prognosis ( 10 ). In this study, Cluster 2 was found to be relevant to lower TSIs ( Supplementary Figure S2C ).…”
Section: Resultsmentioning
confidence: 99%
“…Different metabolism signatures may cause prognosis heterogeneity in ccRCCs, suggesting the possibility to classify ccRCCs from metabolic perspective. To date, variable immune-related classification methods based on gene signatures or immune components in transcriptome studies showed prediction values in ccRCC immunotherapy ( 18 20 ). However, the interplay of immune activity with metabolism is crucial for the regulation of the TME network.…”
Section: Introductionmentioning
confidence: 99%
“…Gui et al. ( 16 ) developed a hypoxia-immune–based multiomics signature since they noticed both the hypoxia and immune status of the tumor microenvironment in ccRCC. A predictive model consisting of 13 glycolysis-related genes was also constructed by Zhang et al.…”
Section: Discussionmentioning
confidence: 99%